(untitled) (Research, Society and Development, 2022)
This study aimed to review the literature on oral manifestations resulting from Crohn’s disease, deepening the knowledge of the dentist to provide, thus, better care to patients with CD. As methodological procedures, a bibliographic review was adopted using the SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect databases, with the assistance of the Mendeley reference manager. The results indicate that oral lesions resulting from Crohn’s Disease include lip edema, granulomatous nodular edema, deep linear ulcerations, mucogingivitis, aphthous ulceration, angular cheilitis and pyosstomatitis vegetans. Oral manifestations of Crohn’s Disease can impair the quality of life of patients who complain of discomfort from these lesions. Therefore, it is essential that health professionals are familiar with these disorders, since oral lesions can serve as fundamental indicators in the early diagnosis of the disease.